Anxiety, depression and treatment adherence among HIV-infected migrants. Issue 8 (3rd August 2019) - Been, S.K.; Schadé, A.; Bassant, N.; Kastelijns, M.; Pogány, K.; Verbon, A.
ABSTRACT: Diagnosing symptoms of psychological distress can be challenging in migrants living with HIV (MLWH) living in Western Europe. We evaluated the Hospital Anxiety and Depression Scale (HADS) as a screening tool for psychological distress. Additionally, the association between psychological distress and adherence to combination Antiretroviral Therapy (cART) was determined. Socio-demographic and clinical characteristics, psychosocial variables, and self-reported adherence to cART data were collected. 306/352 participants completed the HADS. A HADS+ (≥15, at risk for psychological distress) was found in 106/306. The Composite International Diagnostic Interview (CIDI) was completed by 60/106. The HADS was repeated in 58 participants as the time between the first HADS and the CIDI was more than three months. In 21/37 participants with a HADS+ (57%) within three months before the CIDI a diagnosis of depression or anxiety disorder based on the CIDI was found. Participants with a HADS+ were more likely to be non-adherent (71.3% vs. 43.6%). In a large group of MLWH in the Netherlands, 35% were at risk for symptoms of psychological distress. The HADS seems to be a suitable screening tool for MLWH.